AgBi(SO4)(IO3)2: aliovalent substitution induces structure dimensional upgrade and second harmonic generation enhancement. Issue 30 (17th March 2021) - Liu, Hongming; Wu, Qingchen; Liu, Lili; Lin, Zheshuai; Halasyamani, P. Shiv; Chen, Xingguo; Qin, Jingui
Abstract : AgBi(SO4 )(IO3 )2, a Bi-containing 3D sulfate iodate with a similar favorable nonlinear optical framework and enhanced SHG effect, was designed from a 2D iodate by [SO4 ] 2− replacing [IO3 ] − . Abstract : A new 3D noncentrosymmetric mixed-metal sulfate iodate, AgBi(SO4 )(IO3 )2, has been designed based on a 2D iodate of AgBi(IO3 )4 via the aliovalent substitution of [IO3 ] − groups by [SO4 ] 2− groups. Enhancement of the second harmonic generation response (3.0 × KDP to 3.9 × KDP) has been achieved while retaining a favorable NLO framework. This is a novel strategy to upgrade structural dimensions.